1816 : America Rising - Skeen, Carl Edward (Book collections on Project MUSE., 2003)
""The year 1816 found America on the cusp of political, social, cultural, and economic modernity. Celebrating its fortieth year of independence, the country's sense of self was maturing. Americans, who had emerged from the War of 1812 with their political systemsintact, embraced new opportunities. For the first time, citizens viewed themselves not as members of a loose coalition of states but as part of a larger union. This optimism was colored, however, by bizarre weather. Periods of extreme cold and severe drought swept the northern states and the upper south throughout 1816, which was someti.